A versão algorítmica do Lema Local de Lovász com aplicações a problemas de coloração de grafos - Leonardo Angelo Soares da Silva (2018)
The objective of this work is to present the proof of the algorithmic version of the Lovász local lema as well as an improved version of it and apply it to problems of coloring of graphs.